Pemanfaatan Limbah Serbuk Kayu Sengon (Albizia falcataria L) Sebagai Bahan Tambah Pembuatan Paving Block Porous - Al Husayn, Yoga; Rahmawati, Winda; Warji, Warji; Suharyatun, Siti; Febriani, Englang; Maharani, Nia Hikmah (abe.fp.unila.ac.id, 2026)
This study aims to create porous paving blocks with the addition of sengon wood powder as an alternative solution to improve the quality of soil pavement in densely populated areas. The porous paving blocks were made with a cement-to-sand ratio of 1:3, and variations in the addition of sengon wood powder P1 (2%), P2 (4%), P3 (6%), and P4 (8%) of the total material weight of 2200 grams. The resulting porous paving blocks have dimensions of 19.8 × 9.8 × 6 cm with an average weight of 1,859 g. Test results show a density of 1,341–1,921 g/m³, water absorption of 11.002–23.567%, infiltration rate of 0.069–0.146 mm/s, and compressive strength of 2.90–14.32 MPa. The composition of P1 had the best values, with an average compressive strength of 14.315 MPa and an average water absorption rate of 11%, meeting the standards of SNI 03- 0691-1996 Paving Block Grade D. This study shows that porous paving blocks made from sengon wood powder can serve as an alternative pavement material to address waterlogging in urban or densely populated areas and contribute to the utilization of agricultural waste, particularly wood powder waste